Revisiting household coordinates for CCAFS Baseline in the initial regions: East Africa, West Africa and Indo-Gangetic Plains - Kiplimo, Joyce; Förch, Wiebke; Cramer, Laura K.; Mills D (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
In 2010-2012, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) implemented a baseline in 15 sites across three initial target regions: East Africa, West Africa and Indo-Gangetic Plains. The baseline was setup in such a way that the households selected could be a revisited after five and ten years. The aim is to track behavioral change over time in each of the sites by collecting agricultural and household data. Through analyzing the collected data, the aim is to promote a food-secure world through the provision of science-based efforts that support sustainable agriculture and enhance livelihoods while adapting to climate change and conserving natural resources and environmental services.